Menggali Kemampuan Anak Melalui Progresif Learning - Nurwita, Syisva; Haryono, Mimpira; Imran, Ranny Fitria (UNIVED Press, Universitas Dehasen Bengkulu, 2023)
This study aims to analyze the application of progressive learning to explore the abilities of 5-6-year-old children at Dharma Wanita Persatuan Kindergarten in Bengkulu Province. The research approach used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results indicate that the application of progressive learning can holistically improve children's cognitive, language, social-emotional, motor, and creative abilities. Children are actively involved in projects, explorations, discussions, and collaborative activities, enabling them to think critically and creatively, collaborate, express ideas, and develop gross and fine motor skills. The application of this method creates a participatory, contextual, and enjoyable learning environment, thus increasing children's motivation and active participation in the learning process. The research findings confirm that progressive learning plays a significant role in developing children's potential in a balanced and relevant way to meet the demands of 21st-century education.